Quality and efficiency of apple orchard protection affected by sprayer type and application rate - Sedlar, A. D.; Bugarin, R. M.; Nuyttens, D.; Turan, J. J.; Zoranovic, M. S.; Ponjican, O. O.; Janic, T. V. (Spanish Journal of Agricultural Research, 2013)
The goal of this work was to evaluate the potential of reduced application rates in apple trees as well as the potential of selective spray applications by using sensor-based tree detection techniques in Serbian fruit production. Their economical and biological effect was evaluated based on the quality and efficiency of the crop protection and techno-economic analysis. Results showed that during suitable weather conditions and with properly adjusted sprayer settings, a reduced application rate of 381 L ha-1 gave same quality of crop protection as a medium application rate of 759 L ha-1. A two-year efficiency trial on Venturia inaequalis and Podosphaera leucitricha infecting apple also showed that there was no significant difference in crop protection results for different types of orchard application techniques and application rates. The techno-economic analysis showed that selective application should be introduced in practice in areas >3-ha given that the cost of their introduction pays off after 2-3 seasons. Every subsequent season would give a clear economic profit. Besides the economic benefits, selective application technique also has a significant positive ecological effect due to reduction of spray losses and the amount of plant protection products used.